Migrants' capacity as actors of development: do skills matter for economic and social remittances?. (2nd March 2016) - STURGE, GEORGINA; BILGILI, ÖZGE; SIEGEL, MELISSA
Abstract: Highly skilled migrants are presumably in a better position than less skilled ones to contribute to development in their countries of origin, largely by way of economic and social remittances. In this article, we use unique data on first‐generation migrants in the Netherlands to test how economic and social remittances differ by skill level. We find that the highly skilled are more likely to remit, to remit larger amounts and to give advice on education, jobs and health matters. Thus, we identify the highly skilled as having a greater capacity to affect development than have migrants of other skill levels. However, nuances exist with respect to this overall result. We illustrate that the low and medium skilled also show some capacity to affect economic development and that a medium skill level is sufficient to be in a position to transfer significantly more knowledge and skills.